PERMA+4: A Framework for Work-Related Wellbeing, Performance and Positive Organizational Psychology 2.0 - Donaldson, Stewart I.; van Zyl, Llewellyn Ellardus; Donaldson, Scott I. (Frontiers in Psychology, 2022)
A growing body of empirical evidence suggests that PERMA (positive emotions, engagement, relationships, meaning, accomplishments) may be a robust framework for the measurement, management and development of wellbeing. While the original PERMA framework made great headway in the past decade, its empirical and theoretical limitations were recently identified and critiqued. In response, Seligman (2018) clarified the value of PERMA as a framework for and not a theory of wellbeing and called for further research to expand the construct. To expand the framework into organizational contexts, recent meta-analyses and systematic literature reviews showed that physical health, mindset, physical work environments and economic security could be seen as essential contextually relevant building blocks for work-related wellbeing and are therefore prime candidates to expand the PERMA framework for use within organizational contexts. Through expanding the original PERMA framework with these four factors, a new holistic approach to work-related wellbeing and work performance was born: The PERMA+4. As such, the purpose of this brief perspective paper is to provide a conceptual overview of PERMA+4 as holistic framework for work-related wellbeing and work performance which extends beyond the predominant componential thinking of the discipline. Specifically, we aim to do so by providing: (a) a brief historical overview of the development of PERMA as a theory for wellbeing, (b) a conceptual overview of PERMA+4 as a holistic framework for work-related wellbeing and work performance, (c) empirical evidence supporting the usefulness of PERMA+4, and (d) charting a course for the second wave of positive organizational psychological research.